Leveraging OpenSimMPLS: A simulation platform for GoS/MPLS networks in research and education - Manuel Domínguez-Dorado; Javier Carmona-Murillo; David Cortés-Polo; Francisco J. Rodríguez-Pérez; Jesús Galeano-Brajones; Jesús Calle-Cancho (SoftwareX)
Open SimMPLS, an open-source simulator for Multiprotocol Label Switching (MPLS) networks, has been crucial in education, research, and industry for 20 years. It supports software engineering, communication networks, and learning model research, aiding academic projects and publications. Despite new technologies, MPLS remains vital for traffic engineering, ensuring Quality of Service (QoS) for high-demand applications like video streaming and cloud services. It also supports Software Defined Networks (SDN) and Network Functions Virtualization (NFV) by managing data paths and resources in virtualized environments. Open SimMPLS’s impact is evident in community contributions and ongoing studies in MPLS research and application.